Address practice as social action : European perspectives - Norrby, Catrin; Wide, Camilla (Palgrave pivot, 2015)
"How we address one another - whether we use first names, or titles and surnames, for example - says a great deal about who we are, our social relationships and which groups in society we belong to. This edited volume examines address choices in a range of everyday interactions - from radio interviews and service encounters to commercials and internet forums - taking place in Dutch, Finnish, Flemish, French, German, Italian and the two national varieties of Swedish, Finland Swedish and Sweden Swedish. By comparing local, national and cross-border address practices, this volume uncovers both commonalities and differences in the way social meaning is expressed and shaped through address. The chapters also highlight the importance of investigating the daily encounters that make up the social fabric of our lives. This book will be of great interest to researchers of intercultural and cross-cultural communication, interactional sociolinguistics, discourse analysis, conversation analysis and pragmatics"--